Partner relationship from early pregnancy to 30 months postpartum: Gender and parity effects - Canário, Catarina (2016)
The purpose of this study was to analyze individual and dyadic trajectories of change for positive and negative partner relationship from early pregnancy up to 30 months postpartum, while considering time, gender, and parity. Two hundred sixty couples (N 520) recruited from an Obstetrics Outpatient Unit (Portugal) completed a self-report measure of partner relationship at the first, second, and third pregnancy trimester, at childbirth, and again at 3 and 30 months postpartum. Using multilevel modeling, piecewise dyadic growth curve models were performed to predict positive and negative partner relationship through time, gender, and parity. From the first trimester to 3 months postpartum, positive and negative partner relationship decreased, and from 3 to 30 months postpartum positive partner relationship decreased, while negative partner relationship increased, revealing the deterioration of partner relation- ship over time. The positive and the negative partner relationship dimensions were positively correlated within-dyad. From the first trimester to 3 months postpartum the deterioration of partner relationship was worse for women and for second-time parents, whereas from 3 to 30 months postpartum was worse for first-time parents. These findings provided a relevant contribution toward the body of knowledge related with partner relationship quality over pregnancy and the postpartum period. Additionally, the findings presented a relevant practical contribution. Prevention and intervention programs aimed at reducing the risk of deterioration in partner relationship over pregnancy and the postpartum would benefit from including men and women, first- and second-time parents, while addressing the difficulties and challenges that the transition to parenthood poses to partner relationship quality.